FCSIT student online advising appointment system with academic staff's availability viewer - Lo Lee Ching, Lee Ching (Universiti Malaysia Sarawak, (UNIMAS), 2016)
FCSIT student online advising appointment system with academic staff's availability viewer been develop because students must have communication with lecturers. This system can help student found lecturer easily. In this report, it describes planning, analysis, design, implementation and testing, and evaluation of the prototype. System Development Life Cycle (SDLC) is the methodology applied in this system development. Firstly, the problems found in current process appointment between students and lecturer identified. After that, literature reviews is done to determine the feasibility of this project. To elicit user requirements and determine the project scope, design and implementation of the system started. When the system is developed, unit testing, system testing and acceptance testing are carried out. Acceptance testing is done with FCSIT lecturers and students can make appointment easily and more efficient and effective. For further possibility of enhancement limitation and future works of the system are also discussed in the report.